Studies on Neisseria gonorrhoeae cultured in liquid medium. - Eaves, J A (1978)
Experiments were carried out to determine the minimum amount of inoculum of gonococci that is needed to produce growth in ANM liquid medium. This was found to be less than had previously been thought. Minimum inocula were used to study penicillin sensitivity in liquid medium. This work showed that growth occurred at higher concentrations of penicillin with larger inocula. Evidence was also obtained which suggested that in some circumstances penicillin acts bacteriostatically rather than bacteriocidally. It was also shown that growth of gonococci can be inhibited in liquid medium by the presence of hyperimmune serum, the inhibition being more marked in the presence of fresh complement. This work is continuing in the hope that it may provide a basis for a much-needed serological test for gonorrhoea. This would be especially valuable in chronic assymptomatic infections.